Global vulnerability of peatlands to fire and carbon loss - Turetsky, Merritt R.; Benscoter, Brian; Page, Susan; Rein, Guillermo; van der Werf, Guido R.; Watts, Adam (Nature geoscience, 2015)
The amount of carbon stored in peats exceeds that stored in vegetation. A synthesis of the literature suggests that smouldering fires in peatlands could become more common as the climate warms, and release old carbon to the air. Globally, the amount of carbon stored in peats exceeds that stored in vegetation and is similar in size to the current atmospheric carbon pool. Fire is a threat to many peat-rich biomes and has the potential to disturb these carbon stocks. Peat fires are dominated by smouldering combustion, which is ignited more readily than flaming combustion and can persist in wet conditions. In undisturbed peatlands, most of the peat carbon stock typically is protected from smouldering, and resistance to fire has led to a build-up of peat carbon storage in boreal and tropical regions over long timescales. But drying as a result of climate change and human activity lowers the water table in peatlands and increases the frequency and extent of peat fires. The combustion of deep peat affects older soil carbon that has not been part of the active carbon cycle for centuries to millennia, and thus will dictate the importance of peat fire emissions to the carbon cycle and feedbacks to the climate.